The Expression of TGF-b1, p38 MAPK, and ERK-1 Protein in Cleft Affected Tissue of the Lip: An Observational Study - Herman Yosef Limpat Wihastyoko; Erdo Puncak Sidarta (Cell and BioPharmaceutical Institute, 2021)
Background: Cleft lip is a congenital birth defect caused by many proteins. Transforming growth factor (TGF)-β1, p38 mitogen-activated protein kinase (MAPK) and extracellular signal-regulated protein kinase (ERK)-1 are proteins which regulate proliferation and apoptosis role during intrauterine period. This study aimed to observe the expression of these proteins in cleft affected tissue of the lip.Materials and Methods: A descriptive study by examining the TGF-β1, p38 MAPK, and ERK-1 immunohistochemical expression of cleft affected tissue of the lip was conducted. Subjects were patients that were participating for the social event held by Plastic Surgery Department, Faculty of Medicine, Univesitas Brawijaya, on December 3-12, 2012 in Nusa Tenggara Timur. Excess lip mucosa (waste tissue) during the operation were stored in 10% formalin then stained by immunohistochemistry for TGF-β1, p38 MAPK, and ERK-1. We counted the average protein expression under the light microscope with 1000x magnification for 20 different fields of view, randomly.Results: Paraffin blocks from 30 subjects were selected. The mean p38 MAPK expression was found to be highest, with the average of 8 per field of view; followed by the mean TGF-β1 expression, with the average of 5 per field of view; and the mean ERK-1 expression was found to be the lowest, with the average of 2 per field of view. Conclusion: Expression of p38 MAPK and TGF-β1 are higher than ERK-1, suggesting that p38 MAPK is in the same signalling pathway as TGF-β1, while ERK-1 is lower, as its role as anti-apoptotic. This is consistent with several previous studies showing that all proteins took part in the development of cleft lip or craniofacial development. Further study needs to be conducted to determine which protein plays the bigger role.Keywords: cleft lip, TGF-β1, p38 MAPK, ERK-1